Dispersions of Surface Modified Calcium Hydroxide Nanoparticles with Enhanced Kinetic Stability: Properties and Applications to Desalination and Consolidation of the Yungang Grottoes. Issue 1656 (22nd August 2014) - Xiao, Ya; Gao, Feng; Fang, Yun; Tan, Youdan; Liu, Kaiyu; Liu, Shaojun
ABSTRACT: Calcium hydroxide (Ca(OH)2 ) is one of the most interesting materials used to consolidate stone sculptures, monuments, mortars or wall paintings. In this study, we reported on the synthesis and characterization of surface modified Ca(OH)2 nanoparticles as a dispersion with enhanced kinetic stability and the applications for the conservation of sandstone monuments. Uniform hexagonal Ca(OH)2 nanoparticles (∼35nm) were obtained by mixing NaOH and NaCl aqueous solutions at 100∼175 o C using homogeneous-phase reactions. It was further demonstrated that 3-(Methacryloyloxypropane oxygen) trimethoxysilane surfactant agent can significantly reduce agglomeration and simultaneously improve specific surface area of as-synthesized Ca(OH)2 nanoparticles. Brunauer-Emmett-Teller (BET) measurement showed that specific surface area of modified Ca(OH)2 nanoparticles reaches up to ∼48.78m 2 /g, about 2.5 and 3.4 times higher than that of unmodified and commercial ones, respectively. The kinetic stability of Ca(OH)2 despersion can be further enhanced and its viscosity can be decreased by optimizing the ratio of ethanol and n-propanol. Especially, a technique, which combined the Ferroni-Dini method and dispersion of Ca(OH)2 nanoparticles with enhanced kinetic stability, was proposed to effectively desalinate and consolidate the decayed stone, as evidenced by significant decreases of the porosity and concentration of detrimental Cl - and SO4 2- ions in the severely decayed sandstone samples from the Yungang grottoes.